Detection of 2-mm-long strained section in silica fiber using slope-assisted Brillouin optical correlation-domain reflectometry. (27th December 2017) - Lee, Heeyoung; Mizuno, Yosuke; Nakamura, Kentaro
Abstract: Slope-assisted Brillouin optical correlation-domain reflectometry is a single-end-access distributed Brillouin sensing technique with high spatial resolution and high-speed operation. We have recently discovered its unique feature, that is, strained or heated sections even shorter than nominal resolution can be detected, but its detailed characterization has not been carried out. Here, after experimentally characterizing this "beyond-nominal-resolution" effect, we show its usefulness by demonstrating the detection of a 2-mm-long strained section along a silica fiber. We also demonstrate the detection of a 5-mm-long heated section along a polymer optical fiber. The lengths of these detected sections are smaller than those of the other demonstrations reported so far.